Development and evaluation of ready to drink flavoured rice milk beverage with flood affected rice (Oryza sativa L.) - A. MANI, D. SRINATH, K.UMA MAHESWARI, S.SUCHIRITHA DEVI and (The Journal of Research, PJTSAU, 2017)
Rice (Oryza sativa L.) is one of the most important staple food for more than half of the world’s population and influences the livelihood and economies of several billion people. Suzanne et al. (2013) reported that in 2010, approximately 154 million ha of rice was harvested worldwide, of which 137 million ha (88.0%) of the global rice harvested was in Asia. In this 48 million ha (31.0% of the global rice harvested) was harvested in Southeast Asia alone. Paddy loss due to flooding in Bangladesh and India alone amounts to an estimated 4.0 million tons per year, which might be sufficient to feed 30 million people. Much of this paddy is therefore wasted or it deteriorates due to microbial attack. Such produce is often sold at low price causing economical loss to the farmers, especially small and marginal farmers. It does not offer any value-added benefit or incorporate available technology in ways to improve their value. Therefore, the present study was carried out to evaluate the sensory properties of value added product i.e. flavoured rice milk formulated with flood affected rice in comparison with normal rice.